Can polyploidy confer invasive plants with a wider climatic tolerance? A test using Solidago canadensis. Issue 12 (26th May 2020) - Wan, Jizhong; Oduor, Ayub M. O.; Pouteau, Robin; Wang, Beilei; Chen, Luxi; Yang, Beifen; Yu, Feihai; Li, Junmin
Abstract: Polyploidy can cause variation in plant functional traits and thereby generate individuals that can adapt to fluctuating environments and exploit new environments. However, few empirical studies have tested for an association between ploidy level and climatic tolerance of invasive cytotypes relative to conspecific native‐range cytotypes. Here, we used an invasive plant Solidago canadensis to test whether invasive populations had a higher proportion of polyploids, greater height and stem‐base diameter, and occupied a wider range of climatic conditions than conspecific native‐range populations. We also tested whether the invasive populations had overcome genetic founder effects. We sampled a total of 80 populations in parts of the invaded range in China and native range in North America for in situ measurements of plant height and stem‐base diameter in the field and for population genetic and cytotype analyses. To examine climatic correlates, we augmented our field‐sampled data with occurrence records obtained from Global Biodiversity Information Facility. All, except one, of the populations that we sampled in China occurred in a humid subtropical climate. In contrast, the North American populations occurred in humid continental, humid subtropical, and semi‐arid climatic zones. All populations of S. canadensis in China were purely hexaploid, while the North American populations were diploid, tetraploid, and hexaploid. The invasive hexaploids were significantly taller and had a larger stem‐base diameter than native hexaploids. Native hexaploids were significantly taller and had larger stem‐base diameter than native diploids. Climatic correlate assessment found that invasive and native populations occupied different climatic envelopes, with invasive populations occurring in warmer and less seasonal climates than native populations. However, there was no significant correlation between ploidy level and climatic envelope of S. canadensis . Molecular phylogeography data suggest reduced genetic founder effects in the invaded range. Overall, these results suggest that polyploidy does not influence S. canadensis climatic tolerance. Abstract : Climatic envelope assessment found that invasive and native populations occupied different climatic niches, with invasive populations preferring warmer and less seasonal climates than native populations. Molecular phylogeography data provide signatures of reduced genetic founder effects in the invaded range. Polyploidy does not influence Solidago canadensis climatic niche widths.